Hydrographic monitoring of El Niño 97-98 off the coast of southwest Mexico - César O. Monzón; Irina E. Tereshchenko; Anatoliy E. Filonov (Geofísica Internacional, 2003)
Hydrographic data from monthly surveys off the West Coast of Mexico for the period 1996-98 are analyzed. Temperature and salinity profiles of the 1997 summer-fall and the 1998 winter periods differ strongly from similar profiles obtained in 1996. The differences might be due to the input of large volumes of relatively warm and less saline water, with TS features suggesting a Tropical Pacific origin. By January 1998, those water masses had filled the entire upper 90-m layer. The heat storage of the upper 150-m increased to 15.3 GJ/m2, as compared with a January 1996 value of 10.1 GJ/m2. The process which caused sea surface temperature anomalies in El Niño Pacific Equatorial region B occurred one month before the rise in temperature and fall in salinity at our site.